Roadmap proposal for the implementation of telework in Bank operations (Research, Society and Development, 2022)
Due to telework having gained relevance and presented itself as a challenge for organizations due to the Covid-19 pandemic, the objective of this research is to develop a roadmap for the implementation of teleworking in bank operations. It was found through the systematic review of the literature that there are no roadmaps for the implementation of telework. It was used as a criterion for choosing the Bank, one that was in the process of implementing telework in at least one department and that agreed to participate in this research. The DSRM method was selected to structure and validate the solution through an artifact. The roadmap was structured based on the theoretical foundation and the cycle of BPM (Business Process Management). The combination of these elements gave rise to RITO-B (Roadmap for the Implementation of Telework in Bank Operations). RITO-B was validated with bank executives and telecommuting specialists. Although the research has the limitation of having been carried out with a bank and in a pandemic context, the external validation indicated that RITO-B is replicable for the operation of other Banks due to its comprehensive approach and flexibility for adaptations. The contribution of this research is the roadmap that ensures assertive direction, engagement of those involved, serves as a communication tool, reduces implementation risks and adds value by aligning telework with the strategic result. In addition, this study encourages new research on roadmaps for the implementation of telework, expanding its scope of application.